The research station "Vaskiny Dachi", Central Yamal, West Siberia, Russia – a review of 25 years of permafrost studies - Marina O. Leibman; Artem V. Khomutov; Anatoly A. Gubarkov; Yury A. Dvornikov; Damir R. Mullanurov (Fennia: International Journal of Geography, 2015)
The research station "Vaskiny Dachi" on the Yamal Peninsula was established in 1988. Activities aimed at monitoring of permafrost and related environmental features under a relatively low level of nature disturbances caused by gas field development. Cryogenic processes that may affect the environment and their structures have been of primary interest. Landslides are the most common cryogenic processes in Central Yamal in general and also in the proximity of the station. Field surveys of numerous landslides, analysis of their dependence on climatic parameters and their fluctuations resulted in novel classification of cryogenic landslides based on mechanisms of their development. Dating by radiocarbon and dendrochronology allows the separation of cycles of landslide activation. Cryogenic landslides control the development of other processes, such as thermal erosion, river channel erosion and thermokarst. It also affects topography, vegetation pattern, geochemistry of vegetation, ground water and soils. As a result, permafrost parameters, specifically active layer depth and ground temperature, moisture and ice content in the active layer, depend indirectly on landsliding. Monitoring within the framework of the main programs of the International Permafrost Association, such as Circumarctic Active Layer Monitoring (CALM, since 1993) and Thermal State of Permafrost (TSP, since 2011), play an important role among the research activities. From the collected data one can conclude that ground temperature increased on average by about 1 °C since the 1990s. At the same time, active layer fluctuations do not exactly follow the air temperature changes. Spatial changes in ground temperature are controlled by the redistribution of snow which is resulting from strong winds characteristic for tundra environments and the highly dissected relief of Central Yamal. Temporal variations rather depend on air temperature fluctuations but the rate differs in various landscape (environmental) units. While the spatial distribution of active layer depth depends on lithology and surface covers, temporal fluctuations are controlled by ground temperature, summer air temperature, summer precipitation, and in general may contravene climate warming due to specific combination of all factors.